2022
DOI: 10.1038/s41535-022-00516-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal charge transport in topological kagome superconductor CsV3Sb5

Abstract: Nonreciprocal charge transport phenomena are widely studied in two-dimensional superconductors, which demonstrate unidirectional-anisotropy magnetoresistances as a result of symmetry breaking. Here, we report a strong nonreciprocal transport phenomenon in superconducting CsV3Sb5 thin flakes. The second harmonic voltages, mainly originating from the rectification effect of vortex motion, are unambiguously developed with in-plane and out-of-plane magnetic fields, and their magnitudes are comparable to those in n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…4(c), which is attributed to the vortex dynamics nature of nonreciprocal charge transport. [25] This value is much larger compared with known rectification effects in the low-dimensional noncentrosymmetric superconductors like NbSe 2 [24] and the topological kagome superconductor CsV 3 Sb 5 , [19] and competes with the largest one in T d -MoTe 2 thin film. [34,35] It should be noted that for a better comparison among different systems, the normalized coefficient γ = A ⊥ γ instead of γ is more appropriate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4(c), which is attributed to the vortex dynamics nature of nonreciprocal charge transport. [25] This value is much larger compared with known rectification effects in the low-dimensional noncentrosymmetric superconductors like NbSe 2 [24] and the topological kagome superconductor CsV 3 Sb 5 , [19] and competes with the largest one in T d -MoTe 2 thin film. [34,35] It should be noted that for a better comparison among different systems, the normalized coefficient γ = A ⊥ γ instead of γ is more appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that nonreciprocal charge transport here may have two distinct contributions which dominate in different current or magnetic field regimes. [19,21] Figures 4(a) and 4(b) show the maximum second harmonic resistance R 2ω…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, as emphasized in earlier works [36][37][38][39][40] , the structural deformation and symmetry breaking play a significant role in manipulating the properties of AV 3 Sb 5 . Since the CDW features lattice distortions, studies of the lattice degree of freedom can offer insight into the mechanism.…”
Section: Introductionmentioning
confidence: 88%
“…It is found that T c shows a nonmonotonic dependence on the thickness in CsV 3 Sb 5 . 48 Nonreciprocal charge transport behaviors were observed in CsV 3 Sb 5 thin flakes, exhibiting pronounced second harmonic signals in the superconducting state. It may be related to the intrinsic symmetry breaking arising from the unconventional superconducting state.…”
Section: Csv 3 Sbmentioning
confidence: 99%